2018
DOI: 10.5021/ad.2018.30.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Eccrine Poroma with Rapid Growth during Pregnancy: A Case Report and Review of the Literature

Abstract: Eccrine poroma is a benign solitary tumor with acrosyringeal differentiation that usually occurs on the sole or either side of the foot. Rapid growth of eccrine poroma during pregnancy has rarely been reported. We demonstrate a unique case of a 37-year-old pregnant woman who suffered from enlarged eccrine poroma on her left palm, which was tiny for 10 years but suddenly grew to a size of bean-sized reddish brown colored, pedunculated mass during pregnancy. The patient denied a previous history of trauma or inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…[ 2 , 4 ] Etiology of the disease has not been elucidated but it is speculated to have association with radiation, trauma, pregnancy, chemotherapy drugs and infection of human papillomavirus. [ 1 , 2 , 5 ] Our patient had no predisposing or associated factors, which indicated further study is needed to clarify mechanisms facilitating poroma. Recently, a study on molecular basis of eccrine poroma has reported that 88.5% of poroma patients present with recurrent yes-associated protein-mastermind-like protein 2 and yes-associated protein-NUT family member 1 fusion and a WWTRQ-NUT family member 1 fusion was encountered in a single lesion of poroma.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…[ 2 , 4 ] Etiology of the disease has not been elucidated but it is speculated to have association with radiation, trauma, pregnancy, chemotherapy drugs and infection of human papillomavirus. [ 1 , 2 , 5 ] Our patient had no predisposing or associated factors, which indicated further study is needed to clarify mechanisms facilitating poroma. Recently, a study on molecular basis of eccrine poroma has reported that 88.5% of poroma patients present with recurrent yes-associated protein-mastermind-like protein 2 and yes-associated protein-NUT family member 1 fusion and a WWTRQ-NUT family member 1 fusion was encountered in a single lesion of poroma.…”
Section: Discussionmentioning
confidence: 93%
“…[2] There are various nonsurgical treatment including the laser, electrocautery and liquid nitrogen cryotherapy, but surgical excision is the optimal choice of eccrine poroma. [2,5,18] It is worth noting that a regular follow-up is emphasized after excision due to the possibility of malignant transformation and recurrence. [2] In conclusion, the present case manifested with plaque-like appearance, instead of the commonly observed nodules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the eyelid, all cases described were eccrine [3][4][5][6][7][8]. Rare cases associated with radiation therapy and pregnancy have been described [14]. They are rarely multiple [15].…”
Section: Discussionmentioning
confidence: 99%
“…Few reports have described rapid growth of poromas during pregnancy also. [9] Some EPs (approximately 18%) transform into malignant lesions, namely eccrine porocarcinomas. [10] Thus, complete surgical removal and subsequent microscopic examination are necessary.…”
Section: Discussionmentioning
confidence: 99%